(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Orexin receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Orexin receptors [39]) are activated by the endogenous polypeptides orexin-A and orexin-B (also known as hypocretin-1 and -2; 33 and 28 aa) derived from a common precursor, preproorexin or orexin precursor, by proteolytic cleavage and some typical peptide modifications [102]. Currently the only orexin receptor ligand in clinical use is suvorexant, which is used as a hypnotic. Orexin receptor crystal structures have been solved [124, 123].